Towards a Global Tree Assessment. Issue 3 (4th May 2015) - Newton, Adrian; Oldfield, Sara; Rivers, Malin; Mark, Jennifer; Schatz, George; Garavito, Natalia Tejedor; Cantarello, Elena; Golicher, Duncan; Cayuela, Luis; Miles, Lera
Abstract: Although trees have high economic, cultural and ecological value, increasing numbers of species are potentially at risk of extinction because of forest loss and degradation as a result of human activities, including overharvesting, fire and grazing. Emerging threats include climate change and its interaction with the spread of pests and diseases. The impact of such threats on the conservation status of trees is poorly understood. Here we highlight the need to conduct a comprehensive conservation assessment of the world's tree species, building on previous assessments undertaken for the IUCN Red List. We suggest that recent developments in plant systematics, online databases, remote sensing data and associated analytical tools offer an unprecedented opportunity to conduct such an assessment. We provide an overview of how a Global Tree Assessment could be achieved in practice, through participative, open-access approaches to data sharing and evaluation.